Quasi-static tests of RC columns under variable axial forces and rotations. (1st May 2018) - Xu, Guoshan; Wu, Bin; Jia, Dedeng; Xu, Xiaotong; Yang, Ge
Highlights: The significant effects of large variations of the axial load ratio and rotation on the seismic performance of RC columns were analysed by quasi-static tests of five full-scale RC rectangular column specimens. Large variation magnitude of axial loads aggravates the damage of RC columns, causes more severely degrade in the lateral strength, ductility factor, interstory drift angle, secant stiffness. The variable rotations may degrade the lateral strength and cause the reduction of the ultimate ductility, secant stiffness and energy dissipation per cycle. Abstract: The behaviour of reinforced-concrete (RC) elements subjected to axial force and rotation variations in conjunction with lateral displacement variation is considered a highly important topic, but only a few experimental studies investigating this topic have been performed. In this paper, five full-scale RC rectangular columns were tested by quasi-static testing (QST) to investigate the effects of large variation axial forces and rotations on the seismic behaviour of columns. Furthermore, the effects of variable axial forces and rotations on the seismic performance of RC columns in terms of the failure modes, hysteretic loops, skeleton curves, ductility factors, stiffness degradations and energy dissipations are presented and analysed. Based on the QST results, the axial force and rotation variations have significant effect on the seismic behaviour of RC columns. Generally, the variable axial forces and rotations may cause a distinct asymmetrical failure phenomenon in the specimens and reduce the lateral strength and ductility factor. Thus, RC columns should be well designed to account for the adverse effects of variable axial forces and rotations.